The Relationship between Parental Educational Involvement and Chinese Primary School Students’ English Proficiency - Hu, Yichun; Chinokul, Sumalee (NIDA Journal of Language and Communication, 2025)
At present, the influence of Chinese parental involvement on children’s English proficiency cannot be ignored; however, the relationship between Chinese parental involvement and their children’s English language proficiency remains underexplored. This topic is relevant and urgent, not merely for China but also in any context where children are learning English as a foreign language. This study explored two research questions: (1) What is the relationship between parental educational involvement—further divided into sub-categories of Home Literacy Environment (HLE) and school-based participation—and students’ English proficiency? (2) What kinds of parental educational involvement do Chinese parents engage in with their children, and how can these practices be improved? The data were collected from a questionnaire about the current state of parental educational involvement, distributed to 200 sixth-grade students and their parents, along with semi-structured interviews conducted with 12 students, their parents, and three English teachers from a primary school in Chenghua District, Chengdu City. The results showed a positive correlation between parental educational involvement and students’ English proficiency, with a correlation coefficient value of 0.489, p<0.05. Based on the interview data, five types of parental educational involvement were identified. These were categorized, and suggestions for future research are provided.